2022
DOI: 10.3390/en15093328
|View full text |Cite
|
Sign up to set email alerts
|

Do Investment Strategies Matter for Trading Global Clean Energy and Global Energy ETFs?

Abstract: Based on technological innovation and climate change, clean energy has been paid increasing attention to by worldwide investors, thereby increasing their interest in investing in firms that specialize in clean energy. However, traditional energy still plays an important role nowadays, because extreme weather has often occurred in the winters of recent years. We thus explore whether investing the strategies adopted by diverse technical trading rules would matter for investing in energy-related ETFs. By employin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…In practical situations, the widely accepted EMH encounters a challenge from the domain of technical analysis [9,[29][30][31]. The application of technical trading rules can be attributed to herd behavior driven by investor sentiment [32,33], or to stock price overreactions that lead to subsequent price rebounds [34][35][36].…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In practical situations, the widely accepted EMH encounters a challenge from the domain of technical analysis [9,[29][30][31]. The application of technical trading rules can be attributed to herd behavior driven by investor sentiment [32,33], or to stock price overreactions that lead to subsequent price rebounds [34][35][36].…”
Section: Theorymentioning
confidence: 99%
“…An RSI value of 100 (0) indicates that the price is rising (falling) without any decrease (increase). Overbought (oversold) signals are indicated by RSI values of 70 (30) or higher (lower) on the 14-day RSI [40,41]. Furthermore, Shik and Chong [42] note that RSI trading rules can boost currency market risk-adjusted returns; Chong and Ng [43] show that investors can earn higher returns utilizing the RSI trading rule compared to a buy-and-hold strategy.…”
Section: Relative Strength Index (Rsi)mentioning
confidence: 99%
“…Technical analysis is precious in energy and financial markets due to their unique characteristics. These markets are impacted by a variety of factors, such as geopolitical shifts [32], supply and demand dynamics [33], and weather patterns [34], all of which can result in substantial price fluctuations [35][36][37]. This level of volatility makes it challenging to predict future price movements using only fundamental analysis since technical analysis may help investors make better decisions by analyzing price movements [38,39].…”
Section: Theoretical Foundations Of Technical Analysismentioning
confidence: 99%
“…In the short term, investors prefer momentum strategies because they can identify market opportunities and make quick profits. In the long term, on the other hand, investors prefer a contrarian strategy, which aims to buy stocks at a lower price and hold them until their value increases (Abukari and Otchere 2020;Day et al 2022;Mohapatra and Misra 2020). In addition, studies by Kassi et al (2019) showed that market risk has a significant impact on a company's financial performance.…”
Section: Introductionmentioning
confidence: 99%